Green awareness of female consumers towards sustainable products in Indonesia - Wayan Weda Asmara Dewi; Wifka Rahma Syauki (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The purpose of this research is to map how green awareness of female consumers on environmentally friendly products. The green product category can be seen from three indicators, namely; the usefulness of products for the environment, product expectations by consumer desires, and the use of raw materials that do not pollute the environment. Green products include a variety of products, ranging from food, beverages, garments/fashion, to household appliances. The research was conducted using quantitative methods in the form of quantitative surveys to map green consumers and female consumers about their decisions on environmentally friendly products. Based on the results of the quantitative descriptive analysis of the four main indicators of the green awareness variable, it is showing good results. Female consumers are interested in environmental issues and show their concern for the environment.